Nature of potential barrier in (Ca-1/4,Cu-3/4)TiO3 polycrystalline perovskite - Marques, VPB; Bueno, Paulo Roberto [UNESP]; Simoes, A. Z.; Cilense, M.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Leite, E. R. (Elsevier B.V., 2006)
The nonohmic electrical features of (Ca-1/4,Cu-3/4)TiO3 perovskite ceramics, which have very strong gigantic dielectric is believed originate from potential barriers at the grain boundaries. In the present study, we used the admittance and impedance spectroscopy technique to investigate (Ca-1/4,Cu-3/4)TiO3 perovskite ceramics with low nonohmic electrical properties. The study was conducted under two different conditions: on as-sintered ceramics and on ceramics thermally treated in an oxygen-rich atmosphere. The results confirm that thermal treatment in oxygen-rich atmospheres influence the nonohmic properties. Annealing at oxygen-rich atmospheres improve the nonohmic behavior and annealing at oxygen-poor atmospheres decrease the nonohmic properties, a behavior already reported for common metal oxide nonohmic devices and here firstly evidenced for the (Ca-1/4,Cu-3/4)TiO3 perovskite related materials. The results show that oxygen also influences the capacitance values at low frequencies, a behavior that is indicative of the Schottky-type nature of the potential barrier. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: perovskite; nonohmic devices; dieletric devices; varistor